Development and Validation of Free Fall Motion Experiment Kit Based on Arduino UNO and Phyphox Application - Kurniawan, Aziz; Marwoto, Putut; Nugroho, Sunyoto Eko (Jurnal Pendidikan MIPA, 2025)
Abstract: This study aims to develop and validate science teachers' perception of the free fall motion practicum device based on Arduino UNO and the Phyphox Application through the Science Subject Teachers' Deliberation (MGMP) forum. This research method applies the research and development (RnD) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The first step is the analysis of the needs of the problem of misconceptions of free fall motion and the selection of media to be developed; the second step is the design of the development of the device used, namely Arduino UNO and the Phyphox Application in the form of a digital sketch before continuing to the development process. The third step is the development of the Arduino UNO and Phyphox free fall motion kit prototype; the fourth step is the implementation of a data collection trial carried out by a group of volunteer students in the free fall motion practicum and continued with the introduction of the device through the MGMP Science forum. The final evaluation activity is the collection of data from the science teacher perception questionnaire on the developed tool and validating the tool. The results of the testing and development show that Adruino has a slightly lower accuracy level than the phyphox application. These results were obtained from practical activities by a group of students. This may be influenced by development factors and technical settings that can affect the accuracy level of the Adruino practical tool. Each tool has its advantages; Adruino is suitable for training students in coding programming and technology-based learning according to the needs of the 21st century. Meanwhile, Phyphox offers practicality and fast and efficient use. Through practicality testing, both tools provide good and relevant results to improve the quality of learning, especially in the misconception of free fall motion.     Keywords: free fall motion, arduino UNO, phyphox application.